Synthesis and adsorption property of hydrophilic–hydrophobic macroporous crosslinked poly(methyl acryloyl diethylenetriamine)/poly(divinylbenzene) (PMADETA/PDVB) interpenetrating polymer networks (IPNs). Issue 34 (15th April 2015) - Li, Hebing; Fu, Zhenyu; Yang, Li; Yan, Chong; Chen, Limiao; Huang, Jianhan; Liu, You-Nian
<x xml:space="preserve">Abstract</x> A novel hydrophilic–hydrophobic PMADETA/PDVB IPNs possesses a large equilibrium adsorption capacity to salicylic acid.